1992
DOI: 10.1159/000247420
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Urinary Albumin Excretion and Skin Involvement in Patients with Psoriasis

Abstract: The increase in urinary albumin excretion rate (AER), a hallmark of both diabetic nephropathy and hypertension, has also been described in patients affected with diffuse psoriasis. The aim of this study was to investigate whether such an increase is independent of the coexistence of diabetes or hypertension and whether it may be related to the extension and severity of skin lesions. Median AER, determined by radioimmunoassay, was significantly higher in a group of 32 normotensive nondiabetic psoriatic patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 11 publications
(17 reference statements)
3
26
0
3
Order By: Relevance
“…Microalbuminuria, defined as mildly elevated levels of proteinuria (30-200 mg/L), has been reported in patients with mild-moderate psoriasis by Cecchi et al 19 The mean UPER in their cohort of patients with a PASI score greater than 11 was 28.8 mg/24 h, whereas the mean relapse UPER in our GPP group was 560 mg/24 h, which reduced to 140 mg/24 h during remission (reference value, Ͻ150 mg/24 h). The results of Cecchi and colleagues and our own data suggest the presence of renal microvascular hyperpermeability in psoriasis that increases with intensity of skin disease but reverses with successful treatment.…”
Section: Commentmentioning
confidence: 96%
See 1 more Smart Citation
“…Microalbuminuria, defined as mildly elevated levels of proteinuria (30-200 mg/L), has been reported in patients with mild-moderate psoriasis by Cecchi et al 19 The mean UPER in their cohort of patients with a PASI score greater than 11 was 28.8 mg/24 h, whereas the mean relapse UPER in our GPP group was 560 mg/24 h, which reduced to 140 mg/24 h during remission (reference value, Ͻ150 mg/24 h). The results of Cecchi and colleagues and our own data suggest the presence of renal microvascular hyperpermeability in psoriasis that increases with intensity of skin disease but reverses with successful treatment.…”
Section: Commentmentioning
confidence: 96%
“…albuminuria indicates subclinical renal microvascular hyperpermeability, 18 whereas further studies 19 have demonstrated that the extent of albuminuria reflects the degree of psoriatic skin involvement. Microalbuminuria in psoriasis may result from the activity of a circulating permeability factor produced by lesional tissue.…”
Section: Ribonuclease Protection Analysismentioning
confidence: 99%
“…Cecchi et al [21, 22]found a higher urinary concentration of N-acetyl-β- D -glucosaminidase; Madeddu et al [23]also observed a decreased urinary excretion of epidermal growth factor (EGF) in psoriatics (especially in males), whereas the glomerular filtration rate (GFR) was similar compared with age- and sex-matched controls. Urinary EGF correlated inversely with age and directly with urinary kallikrein excretion.…”
Section: Resultsmentioning
confidence: 99%
“…Psorisisin toplumda görülme sıklığı % 1-3 arasındadır 7 . Çocuklarda, erişkinlere benzer şekilde psoriasisin en çok plak tipi (%68,6) görülür, lezyonlar saçlı deride, kulak arkasında, dirseklerde ve dizlerde izlenir 8,9 . Guttat tip psöriazis çocuklarda erişkinlerden daha fazla görülür.…”
Section: Introductionunclassified